Student Learning through Information Communication Technology: A Review - Sah, Gunja Kumari (Orchid Insights: A Multidisciplinary Journal of Orchid College, 2025)
The study focuses on exploring the role of information communication technology (ICT) in enhancing student learning within Nepal’s higher education system. It reviews several studies on factors influencing the global adoption of ICT and highlights its significance for academic growth and development. The study concludes that ICT can significantly boost academic achievement among university students. However, the successful deployment of this technology depends on user acceptance. The research found that factors such as social influence, accessibility, computer self-efficacy, infrastructure, and enjoyment significantly impact the perceived ease of use of ICT systems. Effective use of ICT in the teaching-learning process requires support and knowledge from experts and peers. Students utilize ICT to enhance their education in both virtual and physical classrooms. The findings highlight the potential of ICT to transform the teaching-learning process, promoting a more interactive and engaging educational experience.